Biomarkers of Coagulation and Inflammation in COVID-19–Associated Ischemic Stroke. Issue 11 (November 2021) - Esenwa, Charles; Cheng, Natalie T.; Luna, Jorge; Willey, Joshua; Boehme, Amelia K.; Kirchoff-Torres, Kathryn; Labovitz, Daniel; Liberman, Ava L.; Mabie, Peter; Moncrieffe, Khadean; Soetanto, Ainie; Lendaris, Andrea; et al.
Abstract : Background and Purpose: We sought to determine if biomarkers of inflammation and coagulation can help define coronavirus disease 2019 (COVID-19)–associated ischemic stroke as a novel acute ischemic stroke (AIS) subtype. Methods: We performed a machine learning cluster analysis of common biomarkers in patients admitted with severe acute respiratory syndrome coronavirus 2 to determine if any were associated with AIS. Findings were validated using aggregate data from 3 large healthcare systems. Results: Clustering grouped 2908 unique patient encounters into 4 unique biomarker phenotypes based on levels of c-reactive protein, D-dimer, lactate dehydrogenase, white blood cell count, and partial thromboplastin time. The most severe cluster phenotype had the highest prevalence of AIS (3.6%, P <0.001), in-hospital AIS (53%, P <0.002), severe AIS (31%, P =0.004), and cryptogenic AIS (73%, P <0.001). D-dimer was the only biomarker independently associated with prevalent AIS with quartile 4 having an 8-fold higher risk of AIS compared to quartile 1 ( P =0.005), a finding that was further corroborated in a separate cohort of 157 patients hospitalized with COVID-19 and AIS. Conclusions: COVID-19–associated ischemic stroke may be related to COVID-19 illness severity and associated coagulopathy as defined by increasing D-dimer burden. Abstract : Supplemental Digital Content is available in the text.